2011
DOI: 10.1080/17461391.2011.606840
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and body composition in elite female golf and netball players

Abstract: The aim of this study was to compare bone density and body composition measurements in women participating in elitelevel netball and golf, two sports with contrasting loading characteristics. Bone mineral density (BMD) and body composition were measured using dual-energy X-ray absorptiometry (DXA) in 14 state-level netball players (20.893.4 years), 11 single-digit handicap golf players (22.492.1 years) and a control group (n 018) not training for sport (22.693.6 years). Trunk extensor endurance and grip streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Similar changes in bone mass and bone mineral density have been shown for collegiate female basketball and volleyball players [31]. These results indicate that highly trained female netballers can increase and maintain bone mineral density with adequate mechanical loading well after puberty when skeletal bone is most responsive, albeit by only negligible amounts [30]. It is interesting to note that the bone mineral density of the participant cohort was higher than values reported for male rugby league players [29], and collegiate female basketball and volleyball players [31] emphasising the regular, high-strain mechanical loading that these athletes experience in training and competition [30,33].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Similar changes in bone mass and bone mineral density have been shown for collegiate female basketball and volleyball players [31]. These results indicate that highly trained female netballers can increase and maintain bone mineral density with adequate mechanical loading well after puberty when skeletal bone is most responsive, albeit by only negligible amounts [30]. It is interesting to note that the bone mineral density of the participant cohort was higher than values reported for male rugby league players [29], and collegiate female basketball and volleyball players [31] emphasising the regular, high-strain mechanical loading that these athletes experience in training and competition [30,33].…”
Section: Discussionsupporting
confidence: 74%
“…The absence of an inseason detraining effect in this study's participant cohort might be explained by the short competition period or shorter time-course of altered hormonal and physical states following match-play. Regardless, the increase in bone mineral density in the participant cohort at the end of the competitive season suggests netball players are exposed to a large amount of mechanical loading in training and competition that induces an adaptive bone response [30]. This finding is like research in collision and court-based team sport and supports to some extent the prescription of modified in-season training loads to promote recovery between competition [29,31].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…While golf is generally less physically demanding than most sports, the golf swings generate very high loading of the lumbar spine over a short duration, due to high trunk rotation velocities and trunk muscle contraction forces ( Dorado et al, 2002 ; Myers et al, 2008 ). In the related above researches, Chang et al (2013) reported that the lumbar spine BMD was 6.7% higher in the golf players than in the control subjects. The repetitive short-duration and the high intensity spinal loading associated with the golf swings may produce the bone stain stimuli required to promote the osteoblastic activity ( Burr et al, 2002 ; Robling et al, 2002 ).…”
Section: Discussionmentioning
confidence: 92%
“…3–22% higher BMD in high-impact sports compared to medium- or low-impact sportsTorstveit and Sundgot-Borgen (2005)15 elite male athletes15 non-athletic controlsVolleyball14% and 24% higher BMD at the lumbar spine and femoral neck, respectively, in volleyball players in comparison with non-athletic controlsCalbet et al (1999)14 state-level female athletes18 non-athletic controlsNetball7.8%, 17.3% and 14% higher total body, hip and lumbar spine BMD in the netballers in comparison with the controlsChang et al (2013)50 male highly trained athletes12 non-athletic controls12 judokas14 karate athletes24 water polo playersControl group total body BMD (1.27 g/cm 2 ) was significantly lower than the judo (1.40 g/cm 2 ) and karate (1.36 g/cm 2 ) group but no different to the water polo athletes (1.31 g/cm 2 )Andreoli et al (2001)59 competitive Finnish female athletes25 physical active individuals25 sedentary individuals27 dancers18 squash players14 speed skatersSquash players had significantly higher BMD at the lumbar spine (13%), femoral neck (16.8%), proximal tibia (12.6%) and calcaneus (18.5%) in comparison with the sedentary group. Aerobic dancers also had significantly higher BMD at the loaded sites in comparison with the sedentary group, ranging from 5.3 to 13.5%Heinonen et al (1995)60 athletes15 non-athletic controls15 runners15 swimmers15 triathletes15 cyclistsRunners had significantly higher total body, femoral neck and leg BMD than controls and swimmers as well as higher leg BMD than cyclistsDuncan et al (2002) …”
Section: Bone Mineral Density (Bmd)mentioning
confidence: 99%